Bridging the Gap between the Direct and Hydrocarbon Pool Mechanisms of the Methanol‐to‐Hydrocarbons Process. (30th May 2018) - Chowdhury, Abhishek Dutta; Paioni, Alessandra Lucini; Houben, Klaartje; Whiting, Gareth T.; Baldus, Marc; Weckhuysen, Bert M.
Abstract: After a prolonged effort over many years, the route for the formation of a direct carbon−carbon (C−C) bond during the methanol‐to‐hydrocarbon (MTH) process has very recently been unveiled. However, the relevance of the "direct mechanism"‐derived molecules (that is, methyl acetate) during MTH, and subsequent transformation routes to the conventional hydrocarbon pool (HCP) species, are yet to be established. This important piece of the MTH chemistry puzzle is not only essential from a fundamental perspective, but is also important to maximize catalytic performance. The MTH process was probed over a commercially relevant H‐SAPO‐34 catalyst, using a combination of advanced solid‐state NMR spectroscopy and operando UV/Vis diffuse reflectance spectroscopy coupled to an on‐line mass spectrometer. Spectroscopic evidence is provided for the formation of (olefinic and aromatic) HCP species, which are indeed derived exclusively from the direct C−C bond‐containing acetyl group of methyl acetate. New mechanistic insights have been obtained from the MTH process, including the identification of hydrocarbon‐based co‐catalytic organic reaction centers.